1997
DOI: 10.1002/jmri.1880070116
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Gd‐EOB‐DTPA and superparamagnetic iron oxide particles in the detection of primary liver cancer: A comparative study by alternative free‐response receiver operating characteristic analysis

Abstract: The performance of gadolinium-ethoxybenzyl-diethylenetriaminepentaacetic acid (Gd-EOB-DTPA) and superparamagnetic iron oxide (SPIO) particles in detecting liver cancer was compared using alternative free-response receiver operating characteristic (AFROC) analysis, which allowed observers to indicate both the confidence level and the locations of all perceived abnormalities. Axial T1-weighted MR images (1.5 T) pre/post Gd-EOB-DTPA (25 mumol/kg) injection were obtained for 12 rats with chemically induced liver t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The SIRs of the liver parenchyma, malignant tumors, and benign lesions were comparable between pre-and post-contrast T 2 One more malignant lesion was detected by pre-(46.7z, 85/182) than post-contrast T 2 WI (46.1z, 84/182), but detectability of malignant and benign lesions did not diŠer signiˆcantly between pre-and post-contrast T 2 WI (Figs. 1, 2).…”
Section: T 2 Wimentioning
confidence: 86%
See 3 more Smart Citations
“…The SIRs of the liver parenchyma, malignant tumors, and benign lesions were comparable between pre-and post-contrast T 2 One more malignant lesion was detected by pre-(46.7z, 85/182) than post-contrast T 2 WI (46.1z, 84/182), but detectability of malignant and benign lesions did not diŠer signiˆcantly between pre-and post-contrast T 2 WI (Figs. 1, 2).…”
Section: T 2 Wimentioning
confidence: 86%
“…Considering those previous results, however, most researchers concluded that DWI and T 2 WI after gadoxetic acid administration can be substituted for those before contrast. 2,[15][16][17] We applied 2 non-zero or high b-values (b=500 and 1000 s/mm 2 ) to obtain ADC values. The choice of 2 high b-values over conventional b-values, e.g., b=0 and 1000 s/mm 2 , has some advantage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gadoxetic acid-enhanced MRI is a more sensitive diagnostic tool for detection of HCC than gadopentetate dimeglumine-enhanced MRI. Gadolinium ethoxybenzyl diethylenetriaminepentaacetic acid (gadoxetic acid disodium or Gd-EOB-DTPA) is a recently introduced liver-specific MR contrast agent that has the combined properties of an extracellular space contrast (ECS) agent and a liver-specific agent [1][2][3][4][5][6][7][8]. This combination of gadolinium chelates and superparamagnetic iron oxide particles is considered the most reliable, non-invasive diagnostic MR tool for evaluating hepatocellular carcinoma (HCC), so the dual properties of gadoxetic acid make it a good candidate for the early detection and accurate characterisation of HCC [9][10][11][12].…”
mentioning
confidence: 99%